Boosting nanotoxicity to combat multidrug-resistant bacteria in pathophysiological environments. Issue 11 (29th October 2020) - Westmeier, Dana; Siemer, Svenja; Vallet, Cecilia; Steinmann, Jörg; Docter, Dominic; Buer, Jan; Knauer, Shirley K.; Stauber, Roland H.
Abstract : Low-pH nano-antibiotic formulation may improve therapy of skin infections, overriding the inhibitory impact of biomolecule coronas relevant for practical applications, while bacterial infections in general lead to alkalization of wound areas. Abstract : Nanomaterials are promising novel antibiotics, but often ineffective. We found that nanomaterial–bacteria complex formation occurred with various nanomaterials. The bactericidal activity of NMs strongly depends on their physical binding to (multidrug-resistant) bacteria. Nanomaterials' binding and antibiotic effect was reduced by various pathophysiological biomolecule coronas strongly inhibiting their antibiotic effects. We show from analytical to in vitro to in vivo that nanomaterial-based killing could be restored by acidic pH treatments. Here, complex formation of negatively-charged, plasma corona-covered, nanomaterials with bacteria was electrostatically enhanced by reducing bacteria's negative surface charge. Employing in vivo skin infection models, acidic pH-induced complex formation was critical to counteract Staphylococcus aureus infections by silver nanomaterials. We explain why nano-antibiotics show reduced activity and provide a clinically practical solution.